Kesehatan Mental Guru SD Pasca Pandemi - Puteri, Anggiet Noviana; Suryanto, Suryanto (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
Many changes that occur in the educational climate are suspected to have an influence on the mental health of teachers. To get the maximum learning process required a healthy mental condition of the teacher. This study aims to describe the mental health conditions of elementary school teachers after the pandemic, identify factors that affect the mental health conditions of elementary school teachers and determine efforts to achieve a healthy mental state. This study uses a qualitative method with a phenomenological approach, with interviews. The participants are 3 elementary school teachers in Surabaya. The results shows that three participants need to get support for their mental health conditions, especially in the environmental mastery dimension. Factors that influence the condition are the school system that needs to be understood and adjusted by teachers and the attitude of supervisor. Efforts made to achieve mental health are self-acceptance for individuals and organizing mental health and educational workshops for institutions. Suggestions for teachers and schools are the need for effective two-way communication to support the mental health of teachers.